The girl, the bear and the magic shoes - Donaldson, Julia (China Macmillan Children's Books Uk, 2018)
A magical adventure about a girl, a bear, and some very special new shoes, from the bestselling creators of What the Ladybird Heard.When Josephine leaves the shoe store after buying some lovely new running shoes, she hears an unusual sound